Profitability of Sharia Banks in Indonesia: An Analysis of Third-Party Funds and Murabahah Financing at Bank Muamalat Indonesia - Rosilawati, Weny; Maya Meilia; Putri Fitriyani (Al-Mashrof: Islamic Banking and Finance, 2026)
The profitability of Islamic banks is a key indicator of how effectively banks perform their intermediation function, particularly in mobilizing Third-Party Funds and allocating them through sharia-compliant financing. This study examines the effect of Third-Party Funds and murabahah financing on the profitability of Bank Muamalat Indonesia during the 2015–2024 period. This research applies a quantitative approach using secondary data from the quarterly financial statements of Bank Muamalat Indonesia. The sample consists of 40 quarterly observations selected through purposive sampling. Profitability is measured by Return on Assets, while Third-Party Funds and murabahah financing serve as independent variables. The data were analyzed using multiple linear regression with EViews 10. The findings show that Third-Party Funds have a positive and significant effect on profitability, and murabahah financing also has a positive and significant effect on profitability. Simultaneously, both variables significantly explain profitability, with an R-squared value of 66.69%. The novelty of this study lies in its institutional focus on Bank Muamalat Indonesia as the first Islamic commercial bank in Indonesia and its use of long-term quarterly data to highlight the role of fund mobilization and financing allocation as indicators of sharia intermediation effectiveness.   Keywords: Third-Party Funds; Murabahah Financing; Profitability; Return on Assets; Bank Muamalat Indonesia